Entrepreneurship education literature in the 2000s - Naia, A.; Baptista, R.; Januário, C.; Trigo, V. (Journal of Entrepreneurship Education, 2015)
There seems to be a gap in the literature on entrepreneurship education that prevents it from making stronger contributions towards practice. This study addresses this issue by reviewing the state of the art about entrepreneurship education through the analysis of the contributions made over the 2000s. Theoretical contributions on entrepreneurship education have been increasing and improving in terms of scope and methodology, but there still seems to be a lack of articles that expand knowledge by simultaneously making new theoretical propositions and testing those propositions in new experimental settings. Articles centered on the development of methods, programs, and frameworks often reflect experiences that are context-specific; empirical validation, when offered, is usually limited to those specific contexts. Theory-building and theory-testing are rooted in single paradigms, limiting the generation of more complete and eclectic knowledge. Entrepreneurship education seems to be more focused on what works in the classroom than on developing cutting edge theoretical contributions. Several lines of inquiry are proposed in order to push the boundaries of existing paradigms and trends and improving practice through theory-building. The present work contributes to the literature by providing an overview of the current state of the field, highlighting main trends and gaps. The application of a taxonomy based on the Business and Management literature to analyze theoretical contributions in the field of entrepreneurship education is original and can provide a means for evaluation of progress in the field over time.